Constitutionalizing Sharia: Identity and Independence of Islamic Politics Among Students - Khamami Zada; Mundzeir Suparta; Bambang Ruswadi; Harapandi Dahri; Mualimin Mochammad Sahid (JURIS (Jurnal Ilmiah Syariah), 2022)
The emergence of Islamic political aspirations in Indonesia always occurs along with the development of national politics. It is delivered not only by Islamic elites from Islamic parties and Islamic movements but also by university students. This study explores the Islamic political aspirations of Islamic High School (STAI) students with a focus on the basic issues of the state, Islamic law, political system (democracy/Islamic caliphate), and the way to deliver the aspirations. This is quantitative research in which the data were collected through a representative survey in each province involving 222 university students in the fifth semester in the provincial capital, as the samples were allocated disproportionately to each selected university. This quantitative study was strengthened by qualitative data that were extracted by interviewing the directors of STAI in Padang, Semarang, Jambi, Kupang, Banjarbaru, and Samarinda. The findings of this study showed that Islamic political aspiration among university students was about the aspiration to implement Islamic law as state law in the Islamic caliphate system. The university students did not want democracy as a political system that implements Islamic law. These Islamic political aspirations are not delivered through violence but are expressed constitutionally. This Islamic political aspiration is built by integralistic/conservative religious identity and political independence/autonomy of university students.